Advances in psoriasis research: from pathogenesis to therapeutics - Sugumaran, Dineshwar; Chee, Audrey Hui Yong; Stanslas, Johnson (Elsevier, 2024)
Psoriasis is a chronic inflammatory condition affecting approximately 2 % to 3 % of the global population. The pathogenesis of psoriasis is complex, involving immune dysregulation, hyperproliferation and angiogenesis. It is a multifactorial disease which is influenced by genetic and environmental factors. The development of various therapeutic agents, such as JAK inhibitors, small molecules, and biologics with potential anti-psoriatic properties was possible with the vast understanding of the pathogenesis of psoriasis. Various signalling pathways, including NF-κB, JAK-STAT, S1P, PDE-4, and A3AR that are involved in the pathogenesis of psoriasis as well as the preclinical models utilised in the research of psoriasis have been highlighted in this review. The review also focuses on technological advancements that have contributed to a better understanding of psoriasis. Then, the molecules targeting the respective signalling pathways that are still under clinical trials or recently approved as well as the latest breakthroughs in therapeutic and drug delivery approaches that can contribute to the improvement in the management of psoriasis are highlighted in this review. This review provides an extensive understanding of the current state of research in psoriasis, giving rise to opportunities for researchers to discover future therapeutic breakthroughs and personalised interventions. Efficient treatment options for individuals with psoriasis can be achieved by an extensive understanding of pathogenesis, therapeutic agents, and novel drug delivery strategies.